Presença do gene BRU1 e comportamento diferencial de genótipos de cana-de-açúcar e acessos exóticos a Puccinia melanocephala - Neuber, Ana Caroline [UNESP] (2015)
It is known that the use of molecular markers is an important tool which allows the identification of superior individuals in juvenile stages speeding up the cultivar development process. Sugarcane brown rust caused by the fungus Puccinia melanocephala is among the most important sugarcane diseases. Recently, two diagnostic molecular markers (R12H16, 9O20-F4) flanking the Bru1 gene, which is pointed as the major gene conferring brown rust resistance reported for sugarcane today were publish in the literature. The present study aimed to determine the frequency of the Bru1 gene in sugarcane exotic accessions, Brazilian varieties and elite clones from IAC program as well as to evaluate the efficiency of these markers to identify resistant genotypes. By using the Bru1 markers, it was possible to infer the frequency of Bru1 gene, and compare the results with the phenotypic classification of sugarcane Brazilian varieties and IAC clones (IAC, CTC, SP and RB) for susceptibility to the disease. Moreover, S. spontaneum, S. sinense and S. robustum accessions were artificially inoculated with the fungus P. melanocephala and weekly evaluated in greenhouse conditions. The degree of brown rust susceptibility of the accessions was compared with the presence or absence of Bru1 gene markers. The frequency of the Bru1 gene in the Brazilian varieties was high (75.21%) while only 18% of the sugarcane exotic accessions showed the Bru1 gene. Most of the varieties that presented the gene were classified as resistant. Low marker-phenotypic correlation was observed for the artificially inoculated sugarcane exotic accessions, probably due to the presence of other sources of resistance or failure of the sequence complementarity of the primers in the genome of these accesses. Generally these markers proved to be efficient in the selection of genotypes resistant to brown-rust